2018
DOI: 10.1155/2018/2154361
|View full text |Cite
|
Sign up to set email alerts
|

Increased Duodenal Iron Absorption through Upregulation of Ferroportin 1 due to the Decrement in Serum Hepcidin in Patients with Chronic Hepatitis C

Abstract: Hepatic iron accumulation is generally increased in the chronic hepatitis C (CHC) liver; however, the precise mechanism of such accumulation remains unclear. We evaluated iron absorption from the gastrointestinal tract of patients with CHC and control participants. We measured the expression of a panel of molecules associated with duodenal iron absorption and serum hepcidin levels to determine the mechanism of iron accumulation in the CHC liver. We enrolled 24 patients with CHC and 9 patients with chronic gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Our results showed that hepcidin significantly downregulated several iron transporters and iron transport-associated proteins at mRNA and protein level, especially TfR1, DMT1 and FPN ( Fig 3 ). Corresponding to these results, previous studies also showed that hepcidin suppressed DMT1 and FPN expression in Caco-2, brain microvascular endothelial cells (BMECs) and BKO mice [ 15 , 18 , 22 , 49 , 50 , 56 ]. It has been shown that hepcidin could directly interact with FPN on the basolateral side of enterocytes to activate FPN internalization and degradation [ 57 59 ].…”
Section: Discussionsupporting
confidence: 67%
“…Our results showed that hepcidin significantly downregulated several iron transporters and iron transport-associated proteins at mRNA and protein level, especially TfR1, DMT1 and FPN ( Fig 3 ). Corresponding to these results, previous studies also showed that hepcidin suppressed DMT1 and FPN expression in Caco-2, brain microvascular endothelial cells (BMECs) and BKO mice [ 15 , 18 , 22 , 49 , 50 , 56 ]. It has been shown that hepcidin could directly interact with FPN on the basolateral side of enterocytes to activate FPN internalization and degradation [ 57 59 ].…”
Section: Discussionsupporting
confidence: 67%
“…Hepcidin production and its antiviral action may be reduced by HCV. Low serum hepcidin levels may in turn increase duodenal absorption of iron by up‐regulating duodenal ferroportin, and the increased intracellular iron content may suppress HCV replication in a negative feedback loop . The net effect of these counterbalancing actions may depend on the relative strength of the inherent response to raise hepcidin levels in response to iron overload and the prowess of HCV to circumvent the antiviral action of hepcidin by suppressing transcriptional activity of the HAMP gene …”
Section: Resultsmentioning
confidence: 99%
“…The blots, blocked with 3% BSA for 1 h at room temperature, were incubated with primary antibody (FPN1, 1:1,000, AIT-001; Alomone Laboratories, Jerusalem, Israel; or DMT1, 1:4,000, ab55735; Abcam, Cambridge, United Kingdom; or ␤-actin, 1:1,000, no. 4970; Cell Signaling Technology, Danvers, MA; 12,26,42,50). Following an overnight incubation at 4°C, the blots, washed with Tris-buffered saline-Tween 20 (5 min ϫ 5), were placed in goat anti-rabbit horseradish peroxidase-conjugated secondary antibody (1:20,000) for 2 h at room temperature.…”
Section: Subject Recruitmentmentioning
confidence: 99%